2021
DOI: 10.1080/1828051x.2021.1908860
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of (co)variance components and genetic parameters for pre-weaning body weight traits and Kleiber ratio in Sangsari sheep breed

Abstract: To cite this article: Jamshid Ehsaninia (2021) Estimates of (co)variance components and genetic parameters for pre-weaning body weight traits and Kleiber ratio in Sangsari sheep breed, Italian

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…The coefficient of variation of each trait was between 12 and 23%, indicating that each character had a certain degree The significant effects of birth year, birth month, and birth herd could be attributed to the differences in management, food availability, diseases, and the condition of the climate and raising systems, as described by Ehsaninia (24) for Sangsari sheep and Rashidi et al (14,15) for Kermani sheep. The significant effects of sex and birth type may be attributed to several reasons such as the difference in the endocrine systems of female and male kids.…”
Section: Discussion Fixed E Ectsmentioning
confidence: 90%
See 1 more Smart Citation
“…The coefficient of variation of each trait was between 12 and 23%, indicating that each character had a certain degree The significant effects of birth year, birth month, and birth herd could be attributed to the differences in management, food availability, diseases, and the condition of the climate and raising systems, as described by Ehsaninia (24) for Sangsari sheep and Rashidi et al (14,15) for Kermani sheep. The significant effects of sex and birth type may be attributed to several reasons such as the difference in the endocrine systems of female and male kids.…”
Section: Discussion Fixed E Ectsmentioning
confidence: 90%
“…The results revealed that sex, birth type, birth year and month of kids, birth herd, and age of dam have significant effects on BWT, WWT, ADG, and KR ( p < 0.01) in the present study and were in agreement with the previous reports on Sirohi goats ( 23 ) and Raini Cashmere goats ( 19 ). The significant effects of birth year, birth month, and birth herd could be attributed to the differences in management, food availability, diseases, and the condition of the climate and raising systems, as described by Ehsaninia ( 24 ) for Sangsari sheep and Rashidi et al ( 14 , 15 ) for Kermani sheep. The significant effects of sex and birth type may be attributed to several reasons such as the difference in the endocrine systems of female and male kids.…”
Section: Discussionmentioning
confidence: 99%
“…4.1 The influence of fixed effects on early growth traits and reproductive traits BY, BT, AM, BS, and LS exhibited significant impacts on BWT, WWT, and ADG (30)(31)(32)(33)(34)(35)(36)(37). This could be attributed to variations in breeding management practices and climate changes across different years (38). Seasonal changes influence the nutritional quality of forage, thereby affecting lamb weights at various stages (39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%